Monitoring of River Water Quality in Coban Pelangi and Sungai Metro Using NSF-WQI - Vinaima, Alya Rizki; Rohman, Fatchur (Jurnal Biologi Tropis, 2025)
Rivers are dynamic freshwater ecosystems that play a crucial role in supporting biodiversity, providing clean water, and regulating hydrological cycle. However, their sustainability is increasingly threatened by anthropogenic activities, which increase pollution. Declining water quality contributes to ecosystem degradation and increases risks to human health. This study assessed water quality of Coban Pelangi and Metro River using National Sanitation Foundation Water Quality Index (NSF-WQI) method. Observations were conducted during May–June 2025 at five sampling stations representing different riparian land uses, including protected forest, tourist area, agriculture, and residential zones. Nine parameters were analyzed, including temperature, TDS, turbidity, pH, DO, BOD, phosphate, nitrate, and fecal coliform. Results showed that C1 station in Coban Pelangi protected forest exhibited good water quality (NSF-WQI = 71). In contrast, C2 and C3 station experienced a decline to moderate quality (NSF-WQI = 58–61) due to tourism and agriculture. In contrast, M1 and M2 station located in Metro River agricultural and residential area, showed poor to moderate water quality (NSF-WQI = 49-56). These findings confirm that anthropogenic activities put significant pressure on river ecosystems and cause a decline in water quality. Therefore, a river management policy based on land use and pollution control is needed.